Caracterización mineralógica preliminar de los suelos aledaños a la Mina La Florcita, provincia Sánchez Carrión-Región La Libertad - Montoya, Jenny (2025)
As a result of soil weathering, clays, and iron and aluminum oxides are obtained, which define the soil characteristics. Therefore, it is important to characterize these materials as they accurately reflect the long-term effects of the chemical environment and soil drainage mechanisms. Moreover, they influence many soil properties, especially considering that soils are directly affected by harmful environments such as mining areas. This study presents advancements in the characterization of two horizons within the soil profile of an area called Marmotilla, adjacent to La Florcita Mine, located in the province of Sánchez Carrión, La Libertad Region. The sample extraction point has coordinates Latitude: -7.821713° and Longitude: -78.012394°. The samples were taken from the surface and at 50 cm depth. Mineralogical characterization utilized X-ray diffraction and Mössbauer spectroscopy at room temperature. X-ray diffraction determined the mineral composition in both horizons, identifying quartz, kaolinite, and berlinite. Mössbauer spectroscopy identified three sextets attributed to iron oxides with varying degrees of isomorphic substitution, one Fe^{2+} doublet, and two Fe^{3+} doublets.